Strategi Pemasaran Marketing Mix (7P) Terhadap Penjualan Online dalam Meningkatkan Minat Beli : Studi Kasus pada UD. Kiripik Cawu - Hasti Pramesti Kusnara; Wulan Satriana (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of this research is to determine the implementation of UD's marketing strategy. Kiripik.Cawu on sales in increasing buying interest, knowing the supporting and inhibiting factors in marketing strategies at UD. Kiripik.Cawu on sales in increasing buying interest and finding out the effectiveness of implementing UD's marketing strategy. Kiripik.Cawu on sales in increasing buying interest. Data analysis uses qualitative descriptive methods and marketing strategies use the marketing mix strategy (7P). The results of this research indicate that UD. Kiripik.Cawu has implemented a marketing mix strategy, namely Product, Price, Promotion, Process, people, Place and physical evidence, Products produced by UD. Kiripik.Cawu has various variations so that it can suit consumer tastes. implementing pricing strategies, UD. Kiripik.Cawu can compete with other product businesses because it offers affordable prices. UD. Kiripik.Cawu is effective in marketing products and increasing production and sales while maintaining product quality, price and innovative product variations.